Anomalous origin of the left coronary artery from the pulmonary artery presenting as dilated cardiomyopathy - Ali Rahmi Bakiler; Kayı Eliaçık; Seda Köse; Yüksel Atay (KARE Publishing, 2013)
Anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital anomaly and one of the causes of myocardial ischemia. It often presents with atypical signs and symptoms, especially in childhood. In this case report, an 11-year-old girl presented with dilated cardiomyopathy (DCM) in our clinic and was followed for 5 years, echocardiography (ECHO) showed multiple left to right shunts on the interventricular septum (IVS) the confirmation of which was done by multislice computed tomography (MSCT) and coronary angiography. Therefore, we suggest that ALCAPA be suspected in patients diagnosed with DCM.